Fabrication of Polyvinylidene Difluoride Membrane with Enhanced Pore and Filtration Properties by Using Tannic Acid as an Additive - Mulyati, S. (MDPI, 2022)
Potential use of tannic acid (TA) as an additive for fabrication of polyvinylidene difluoride (PVDF) membrane was investigated. The TA was introduced by blending into the dope solution with varying concentrations of 0, 1, 1.5, and 2 wt. The prepared membranes were characterized and evaluated for filtration of humic acid (HA) solution. The stability of the membrane under harsh treatment was also evaluated by one-week exposure to acid and alkali conditions. The results show that TA loadings enhanced the resulting membrane properties. It increased the bulk porosity, water uptake, and hydrophilicity, which translated into improved clean water flux from 15.4 L/m2.h for the pristine PVDF membrane up to 3.3Ã for the TA-modified membranes with the 2 wt TA loading. The flux recovery ratio (FRR) of the TA-modified membranes (FRRs = 78â83) was higher than the pristine one (FRR = 58.54), with suitable chemical stability too. The improved antifouling property for the TA-modified membranes was attributed to their enhanced hydrophilicity thanks to improved morphology and residual TA in the membrane matric. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.